P2.033 Isolation of Neisseria Gonorrhoeae from the Tonsils and Posterior Oropharynx Using Culture. (13th July 2013) - Bissessor, M; Whiley, D; Bradshaw, C S; Fairley, C K; Lee, D M; Snow, A; Horvath, L; Chen, M
Abstract : Background: Culture is insensitive for detecting pharyngeal gonorrhoea but is critical for determining antimicrobial resistance. Sampling technique appears to be important for optimal isolation of pharyngeal gonorrhoea, however, there are no published studies on the specific anatomical areas within the pharynx that should be targeted. The aim of this study was to compare isolation rates of gonorrhoeafrom the tonsils and posterior oropharynx. Method: Men who had sex with men attending the Melbourne Sexual Health Centre who screened positive for pharyngeal gonorrhoea using modified Thayer Martin medium were recalled and reswabbed prior to treatment. The repeat swabs consisted of careful swabbing from both tonsils followed by swabbing of the posterior oropharynx using a separate swab. These were plated onto separate media and cultured. Results: To date 61 MSM who screened positive for pharyngeal gonorrhoea have been recalled for repeat swabbing. The median interval between the initial positive screening test and repeat swabbing was 7 days. The positivity rates from the repeat swabs of the tonsils and posterior oropharynx were 69% (n = 41) and 52% (n = 32) respectively. The repeat tonsillar and posterior oropharyngeal swabs were both positive in 51% (n = 31) of men and were both negative in 30% (n = 18) of men. Eleven men (18%) had positive tonsillar and negative oropharyngeal results while one man had positive oropharyngeal and negative tonsillar results (p < 0.01). The results of concurrent nucleic acid amplification testing will be presented. Conclusion: These interim study results indicate that Neisseria gonorrhoea e can be cultured from the tonsils as well as the posterior oropharynx. While the positivity rate from tonsillar swabbing was higher than swabbing of the posterior oropharynx, sampling from only one of these sites had poor sensitivity. Many cases of pharyngeal gonorrhoea appear to be transient and self limiting.